Sports economics - Blair, Roger D. (Cambridge : Cambridge University Press, 2012)
Sports Economics, the most comprehensive textbook in the field by celebrated economist Roger D. Blair, focuses primarily on the business and economics aspects of major professional sports and the NCAA. It employs the basic principles of economics to address issues such as the organization of leagues, pricing, advertising and broadcasting as well as the labor market in sports. Among its novel features is the candid coverage of the image and integrity of players, teams, managers and the leagues themselves, including cases of gambling, cheating, misconduct and steroids. Blair explains how economic decisions are made under conditions of uncertainty using the well-known expected utility model and makes extensive use of present value concepts to analyze investment decisions. Numerous examples are drawn from the daily press. The text offers ample boxes to illustrate sports themes, as well as extensive use of diagrams, tables, problem sets and research questions.
Introduction to sports economics -- The business of sports -- Sports leagues and organizations -- Competitive balance -- Pricing decisions -- Advertising in the sports industry -- The market for sports broadcasting rights -- Insuring player talent -- Sports leagues and antitrust policy -- Sports gambling -- Cheating in sports -- Misconduct and discipline -- Steroids and other performance-enhancing drugs -- Competing for sports franchises and events -- Economic impact of sports events -- Financing sports facilities -- Salary determination : Competition and monopsony -- The National Collegiate Athletic Association as a collusive monopsony -- Salary determination : Bidding and bargaining -- Economic value of multiyear contracts -- Final offer arbitration in major league baseball -- Players' unions and collective bargaining -- The role of sports agents -- Should an athlete turn pro "early"? -- Discrimination in sports.
Title from publisher's bibliographic system (viewed on 18 Jul 2016).
Keywords: elektronické knihy; electronic books; Sports -- Economic aspects; Professional sports -- Economic aspects